False Positive Radioiodinated Metaiodobenzylguanidine (123I-MIBG) Uptake in Undifferentiated Adrenal Malignant Tumor - Hee Soo Jung; Seok Jun Moon; Yun Mi Kim; Hye Rim Kang; Seok Mo Lee; Soo Jin Jung; Seok Jin Choi; Tae Kyoon Kim; Min Jeong Kwon; Jeong Hyun Park; Soon Hee Lee (Case Reports in Oncological Medicine)
123I-Metaiodobenzylguanidine (123I-MIBG) scintigraphy is a widely used functional imaging tool with a high degree of sensitivity and specificity in diagnosis of pheochromocytoma. However, rare cases of false positive reactions have been reported. A 67-year-old male patient was admitted with epigastric pain. Abdominal computed tomography (CT) revealed a heterogeneous left adrenal mass 6 cm in diameter; following hormone testing, 123I-MIBG scintigraphy was performed to determine the presence of pheochromocytoma, which confirmed eccentric uptake by a large left adrenal gland mass. Chest CT and PET-CT confirmed metastatic lymphadenopathy; therefore, endobronchial ultrasound transbronchial needle aspiration was performed. Metastatic carcinoma of unknown origin was suspected from a lymph node biopsy, and surgical resection was performed for definitive diagnosis and correction of excess hormonal secretion. A final diagnosis of undifferentiated adrenal malignant tumor was rendered, instead of histologically malignant pheochromocytoma, despite the uptake of 123I-MIBG demonstrated by scintigraphy.